Digital’s cleaving power and Its consequences - Floridi, L (Springer, 2017)
The digital is deeply transforming reality. This is much obvious and uncontroversial. The real questions are why, how, and so what. In each case, the answer is far from trivial and definitely open to debate. To explain the ones I find most convincing, let me start in medias res, that is, from the “how”. It will then be easier to move backwards, to understand “why”, and then forward, to deal with the “so what”.